1981
DOI: 10.1017/s0003356100025198
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of feedblocks as a means of providing supplementary nutrients to ewes grazing upland/hill pastures

Abstract: A series of trials was conducted to measure the extent of individual variation in feedblock intake for ewes on upland/hill farms. From 15 flocks on nine farms 4284 ewes were selected with a range of environmental conditions and levels of performance. Ewes were given either Rumevite, Norbloc or Wintawell feedblocks containing chromic oxide. Faecal grab samples were taken per rectum from individual ewes and analysed for their chromium content to obtain estimates of feedblock consumption.The results showed that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
2
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 2 publications
5
19
2
1
Order By: Relevance
“…3 as compared with intake of block 1 in the 12-d trial could be related to the difference in block composition. However, other research has shown i) that lasalocid did not affect intake of free-choice mineral (Pitman and Pate 1984;Rode et al 1994) and ii) that differences in CP content among molasses blocks must be far greater than the 25 vs. 22% in the present study before they would affect feeder attendance or intake (Lobato and Pearce 1980;Ducker et al 1981). Relative hardness of the blocks can also affect block intake (Zhu et al 1991;McAllister and Olson, unpublished data) and an effort was made to ensure that all blocks were of equal hardness in our study.…”
Section: Molasses Blocks (Exp 3)contrasting
confidence: 62%
“…3 as compared with intake of block 1 in the 12-d trial could be related to the difference in block composition. However, other research has shown i) that lasalocid did not affect intake of free-choice mineral (Pitman and Pate 1984;Rode et al 1994) and ii) that differences in CP content among molasses blocks must be far greater than the 25 vs. 22% in the present study before they would affect feeder attendance or intake (Lobato and Pearce 1980;Ducker et al 1981). Relative hardness of the blocks can also affect block intake (Zhu et al 1991;McAllister and Olson, unpublished data) and an effort was made to ensure that all blocks were of equal hardness in our study.…”
Section: Molasses Blocks (Exp 3)contrasting
confidence: 62%
“…However, the use of a radioactive substance such as tritiated water is severely constrained by concerns for human health and the environment, while deuterium is costly for large ruminants or large numbers of animals. Digesta markers that are quantitatively excreted in the faeces, such as chromic oxide (Foot et al 1973;Lobato et al 1980;Ducker et al 1981) and ytterbium (Curtis et al 1994), have been used to measure supplement intake. However, since these markers require either complete collection of faeces for several days (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Eggington et al (1990) found even bigger variation -they described the range in acceptance of salt block between 10 g and 835 g·day -1 . Apart from variations in the amount of lick intake, there were variations in the acceptance of molasses blocks (of identical composition) made by different manufacturers (Ducker et al 1981;Kendall et al 1983). We may say that many factors play a role in the intake of mineral lick.…”
Section: Resultsmentioning
confidence: 99%